Acute hemorrhagic leukoencephalitis unresponsive to aggressive immunosuppression. Issue 1 (11th January 2017) - Sureshbabu, Sachin; Babu, Raghunath; Garg, Amit; Peter, Sudhir; Sobhana, Chindripu; Mittal, Gaurav
Abstract: Acute hemorrhagic leukoencephalitis is the most fulminant form of the inflammatory demyelinating diseases of the central nervous system. The ideal management of this condition is debatable, but aggressive immunosuppressive regimens are mostly recommended. A 19‐year‐old man presented with sudden onset altered sensorium, seizures, and focal neurological deficit after 2 weeks of fever and malaise. His magnetic resonance imaging showed an asymmetric predominantly posteriorly located T2 hyperintense white matter lesion with hemorrhage evident on gradient recalled echo sequences along with profound edema and mass effect. Decompressive craniectomy, pulse methylprednisolone, intravenous immunoglobulin, plasma exchange, cyclophosphamide and rituximab were tried over the next 24–48 h, which failed to arrest the aggressicve course of the illness. The clinical diagnosis and management of acute hemorrhagic leukoencephalitis can be challenging. Early recognition and aggressive treatment offers the only hope of meaningful survival in these patients. Abstract : The catastrophic presentation of hemorrhagic leukoencephalitis is described in a young boy . A highly aggressive immunosuppressive regimen and efforts to lower the raised intracranial pressure was followed but didnot succeed ultimately.